The case of orbital lymphatic malformation in child treated with surgery - Niwald, Anna Maria; Daszyńska, Monika; Piasecka, Katarzyna; Kobielski, Artur; Kobos, Józef; Grałek, Mirosława (Klinika Oczna / Acta Ophthalmologica Polonica, 2019)
The authors described the diagnostic management of a 12-year-old child with a sudden onset of a rare orbital lymphatic malformation and its surgical treatment. The malformation was diagnosed based on clinical manifestation and diagnostic imaging (ultrasound, magnetic resonance imaging). The surgical excision of the anterior orbital aspect of the malformation was performed with uneventful postoperative period and a good clinical effect.